The janissary tree [compact disc, unabridged] - Goodwin, Jason, 1964- (Tantor Media, 2007)
When the Ottoman Empire of 1836 is shattered by a wave of political murders that threatens to upset the balance of power, Yashim, an intelligence agent and a eunuch, conducts an investigation into clues within the empire's once-elite military forces.